Perceived Research Environment and Research Burnout in Indonesian Academics: The Moderator Role of Research Importance - Dian R. Sawitri (Journal of Educational, Health and Community Psychology, 2020)
Research burnout is an individual’s emotional condition correlated with long-term pressures in the processes of academic research and publication. Nowadays, involve in more research activities in order to be more research productive is expected among higher education academics. These expectations put a lot of pressure on higher education academics to publish and also to generate grant money. Those who cannot meet the expectations may feel a sense of research burnout. We surveyed 290 Indonesian academics (49.8% female, mean age = 42.30 years) from several higher degree institutions in Indonesia. We used scales of research importance, perceived research environment, and research burnout. Hierarchical regression analyses demonstrated that research importance moderated the relationship between perceived research environment and research burnout. For those who have low research importance, perceived research environment was positively correlated with burnout, but for those who have high research importance, perceived research environment was negatively correlated with burnout.